Antimicrobial use in wean to market pigs in the United States assessed via voluntary sharing of proprietary data. Issue 1 (17th November 2020) - Davies, Peter R.; Singer, Randall S.
Abstract: Data on antimicrobial use were collected for the 2016 and 2017 calendar years from swine producers in the United States. Nine large systems, collectively producing over 20 million market pigs annually, voluntarily provided data to advance understanding of antimicrobial use in the industry and to support antimicrobial stewardship initiatives. The scope of the study was limited to growing pigs, and the granularity of data varied across the systems. Data were summarized both qualitatively and quantitatively by antimicrobial class, active ingredient and route of administration (injection, water and feed). Data on the purpose of administration, doses and durations of administration were not available, but some information was provided by the responsible veterinarians. Aggregate data were similar both qualitatively and quantitatively in 2016 and 2017, although marked changes between years were evident within systems for some antimicrobials. Antimicrobial use (by weight) was dominated by the tetracycline class (approximately 60% of total use). Antimicrobials in classes categorized as critically important constituted 4.5% and 5.3% of total use in 2016 and 2017, respectively. In both years, fluoroquinolone (0.23%, 0.46%) and 3rd generation cephalosporin (0.15%, 0.11%) use collectively accounted for <1% of total use. Administration was predominantly oral in feed and water, and injection comprised approximately 2% of use overall, but around 12% for critically important antimicrobials. There was considerable variability among systems in patterns of antimicrobial use. This pilot project demonstrates the feasibility of acquiring antimicrobial use data via voluntary sharing. It is currently being expanded among larger swine production systems, and further efforts to enable confidential data sharing and benchmarking for smaller producers are being pursued by the swine industry. Recognized biases in the data caution against over‐interpretation of these data as an index of national use.